The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fphar.2021.634477
|View full text |Cite|
|
Sign up to set email alerts
|

Polypharmacy to Mitigate Acute and Delayed Radiation Syndromes

Abstract: There is a need for countermeasures to mitigate lethal acute radiation syndrome (ARS) and delayed effects of acute radiation exposure (DEARE). In WAG/RijCmcr rats, ARS occurs by 30-days following total body irradiation (TBI), and manifests as potentially lethal gastrointestinal (GI) and hematopoietic (H-ARS) toxicities after >12.5 and >7 Gy, respectively. DEARE, which includes potentially lethal lung and kidney injuries, is observed after partial body irradiation >12.5 Gy, with one hind li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…These models enable analyses to be conducted under standardized conditions and can yield conclusive evidence regarding the proposed sex-specific radiation sensitivity. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 33 In this study, we performed a robust 30-day animal studies with 6 escalating radiation doses (7–9 Gy) and find that females are more radioresistant than males. Probit analysis of the lethal dose curves shows that LD50/30 is 7.76 Gy for male mice and 8.08 Gy for female mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These models enable analyses to be conducted under standardized conditions and can yield conclusive evidence regarding the proposed sex-specific radiation sensitivity. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 33 In this study, we performed a robust 30-day animal studies with 6 escalating radiation doses (7–9 Gy) and find that females are more radioresistant than males. Probit analysis of the lethal dose curves shows that LD50/30 is 7.76 Gy for male mice and 8.08 Gy for female mice.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, DEARE studies also disclosed different effects on male and female mice. 24 , 25 , 26 This implies that sex-related factors may play a role in the long-term response to radiation exposure. Nonetheless, the associated cellular and molecular mechanisms for these variations in sensitivity and long-term response to radiation exposure remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease following irradiation develops clinically, and both PBI rat ( 23 ) and PBI NHP ( 20 ) models develop K-DEARE either concurrent to, or following, L-DEARE. In the C57L/J mouse model described herein, there is a lack of evidence for the development of K-DEARE, and this is consistent with the similar C57L/J model developed by Gibbs et al ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that major differences in vasculopathy, inflammation, oxidative imbalance, and senescence between the heart and kidney suggest the need for different MCMs in different organs to be administered at different times post-irradiation. Further support for the concept of a time-dependent polypharmacy approach to mitigating ARS and DEARE comes from a study employing PBI in a rat model (150). In this study, a triple combination of H-ARS mitigators were used to support survival through H-ARS.…”
Section: Populations With Comorbidities or Lifestyle Risksmentioning
confidence: 99%